2009
DOI: 10.1089/ten.tea.2008.0568
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Treatment Overcomes Time-Related Degrading Bioactivity of Titanium

Abstract: The shelf life of titanium implant products, that is, a possible time-related change of their bioactivity, has rarely been addressed. The objective of this study was to examine the bioactivity of newly processed and aged titanium surfaces and determine whether ultraviolet (UV) light treatment of the titanium surface restores the possible adverse effects of titanium aging. Titanium disks, either acid-etched or sandblasted, were used immediately after processing (fresh surface) or after storing in dark for 4 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
103
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 19 publications
11
103
1
Order By: Relevance
“…This time-dependent degradation of biological activity on the titanium surface was statistically correlated with an increase in the occupancy of carbon. In addition, ultraviolet treatment of aged surfaces increased bioactivity to a level greater than that observed on freshly prepared surfaces [34]. UV-treatment resulted in a clear reduction in the atomic occupancy of carbon on the titanium surface (from over 50% to less than 20%), a proven basic premise for bio-activation by UV-photofunctionalization, together with a change from low wettablity to super-hydrophilicity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This time-dependent degradation of biological activity on the titanium surface was statistically correlated with an increase in the occupancy of carbon. In addition, ultraviolet treatment of aged surfaces increased bioactivity to a level greater than that observed on freshly prepared surfaces [34]. UV-treatment resulted in a clear reduction in the atomic occupancy of carbon on the titanium surface (from over 50% to less than 20%), a proven basic premise for bio-activation by UV-photofunctionalization, together with a change from low wettablity to super-hydrophilicity.…”
Section: Discussionmentioning
confidence: 93%
“…Acta Biomater Our previous studies demonstrated an increase in the occupancy of carbon and a reduction in osteoblast attachment and protein absorption on bulk titanium surfaces over storage-time in a sterile atmosphere after surface preparation including machining and acid-etching, which was termed the "biological aging of titanium" [32][33][34]. This time-dependent degradation of biological activity on the titanium surface was statistically correlated with an increase in the occupancy of carbon.…”
Section: Discussionmentioning
confidence: 99%
“…Other reported methods of managing carbon compound adhesion are ultraviolet treatment 33) , storage in saline solution 34) , and gamma-ray irradiation 35) . Ultraviolet treatment is reported to cause physicochemical changes such as changing the titanium surface from hydrophobic to hydrophilic 36) , causing the carbon atom ratio to decrease 37,38) . However, this method has drawbacks in that decomposed carbon compounds remain on the surface, high-concentration ozone gas generated by the ultraviolet rays must be removed, and the apparatus is expensive.…”
Section: Push-in Testmentioning
confidence: 99%
“…The rate and degree of protein adsorption, cell attachment, and cell proliferation decreased by 30%-80% on 4-week-old titanium surfaces compared with new surfaces. [1][2][3] Progressive accumulation of hydrocarbons, and time-related disappearance of hydrophilic properties and electrostatic positivity on titanium surfaces are thought to be responsible for this biological aging. 1,4,5 Currently, there are no effective means to prevent the biological aging of titanium.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of bioactivity and osteoconductivity of UV-treated titanium surfaces exceeds the levels of newly prepared titanium surfaces. 2,3 UV treatment reverses the time-dependent physicochemical changes of titanium surfaces. 4,5 UV treatment of aged titanium surfaces decomposes hydrocarbons by inducing photocatalytic activity and restores superhydrophilicity.…”
Section: Introductionmentioning
confidence: 99%